2010
DOI: 10.4196/kjpp.2010.14.5.325
|View full text |Cite
|
Sign up to set email alerts
|

Epigallocatechin-3-gallate Regulates NADPH Oxidase Expression in Human Umbilical Vein Endothelial Cells

Abstract: Vascular NADPH oxidase plays a pivotal role in producing superoxide in endothelial cells and thus acts in the initiation and development of inflammatory cardiovascular diseases such as atherosclerosis. Epigallocatechin-3-gallate (EGCG), the major catechin derived from green tea, has multiple beneficial effects for treating cardiovascular disease but the effect of EGCG on the expression of vascular NADPH oxidase remains unknown. In this study, we investigated the mechanism(s) by which EGCG might inhibit the exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 31 publications
0
17
0
Order By: Relevance
“…An antioxidative function has been proposed as one of the mechanisms for the anti‐tumor and anti‐atherogenic effects of catechins (da Silva et al ., ; Zhang et al ., ). In a study of vascular NADPH oxidase, EGCG reduced the expression of NADPH oxidase and ROS production in human umbilical vein endothelial cells (Ahn et al ., ). NADPH oxidase is also considered a major source of ROS in TGF‐β1 induced NPDFs.…”
Section: Discussionmentioning
confidence: 97%
“…An antioxidative function has been proposed as one of the mechanisms for the anti‐tumor and anti‐atherogenic effects of catechins (da Silva et al ., ; Zhang et al ., ). In a study of vascular NADPH oxidase, EGCG reduced the expression of NADPH oxidase and ROS production in human umbilical vein endothelial cells (Ahn et al ., ). NADPH oxidase is also considered a major source of ROS in TGF‐β1 induced NPDFs.…”
Section: Discussionmentioning
confidence: 97%
“…Moreover, the role of Ang II in mediating HUVEC responses to oxidative stress has been investigated [31,32]. Although past studies have confirmed that EGCG inhibits Ang II-induced adhesion molecule levels in HUVECs [33,34], understanding of the underlying molecular mechanisms remains limited. Our study suggested that EGCG is able to attenuate Ang II-enhanced HUVEC injury, at least in part, via the activation of Nrf2 signaling.…”
Section: Discussionmentioning
confidence: 99%
“…For this study primary vascular endothelial cells (human umbilical vein endothelial cells; HUVEC) have been used rather than endothelial cell lines, which have been reported to vary in characteristics quite dramatically when compared to ex vivo tissues. HUVEC are well characterized, relatively easily accessible, primary cells that have been reported to exhibit key endothelial cell functions, and are extensively used in the study of the effects of dietary chemicals upon cardiovascular biology and diseases . Specifically, we have assessed the effects of quercetin on NO˙ availability, O 2 ·− production and NADPH oxidase subunit protein levels and activity.…”
Section: Introductionmentioning
confidence: 99%